PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT. ACE HARDWARE INDONESIA TBK TAHUN 2012-2021 - Randhy Agusentoso; Sri Retnaning Sampurnaningsih; Dewi Nari Ratih Permada (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to determine the effect of cash collection and turnover on profitability at PT. ACE Hardware Indonesia Tbk. Method used in this study. This research was conducted using processed data. The population of this study is the annual financial statements of PT. ACE hardware Indonesia Tbk Year 2012-2021. The sampling method uses Purposive Sampling technique. The research method used in this study is the multiple linear regression method, which consists of several submissions, namely descriptive statistics, multiple linear regression, partial tests, simultaneous tests, and coefficients of determination. The results of this study show that the results of the partial test of cash turnover have a positive and significant effect on Return On Assets with significance (0.02 < 0.05), Receivables turnover does not have a significant effect on Return On Assets with significance (0.470 > 0.05), while Debt To Equity has a negative and significant effect on Return On Assets with significance (0.002 < 0.05). The results of the simultaneous test of cash collection, receivables and Debt To Equity simultaneously affect perofitability. The results of the statistical F test study amounted to (0.002 < 0.05) which means that there is a significant influence simultaneously between the independent variable and the dependent variable. This shows that cash turnover, receivables turnover and debt to equity are so important in relation and influence on profits, because the success of a company in generating profits is obtained from cash and receivables that are well managed and efficient.